Tarbiyatul Aulad Fil Islam: Breaking the Chain of Promiscuous Sex among Teenagers - Doni Saputra (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2022)
This study explores the sexuality education that exists among adolescents. This sexuality education does not mean providing sex education to adolescents, but rather education related to the limits that adolescents allow in living life so that adolescents understand and do not fall into things that can destroy their future. In addition to adolescents, educators, teachers, and parents are also expected to be able to understand the importance of sex education in adolescents. This research uses a qualitative research approach to literature. The focus of this study is sex education delivered to adolescents. The source of this research data is sourced from the book of Tarbiyatul Aulad Fil Islam. The data analysis technique in this study is Contact Analysis. The result of this research is that in the Book of Tarbiyatul Aulad Fil Islam, it is explained that before an educator delivers sex education, the educator must first form his character following applicable norms. Among other things, it must be sincere, piety, knowledgeable, polite, and easy to forgive. sex education to adolescents in the form of ethics of asking permission to enter the room, ethics of seeing the opposite sex, keeping children away from behavior that invites martyrdom, educating sharia laws related to adolescence and adulthood, directing adolescents to be able to restrain themselves (from sexual desire) when unable to marry and educating children about marriage and sex.